The art of mooting : theories, principles and practice - Thomas, Mark; Cradduck, Lucy; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2019)
"Advocacy skills, which are learnt in the moot court, as a precursor to the effective communication of persuasive legal argument, are essential for those seeking a career in law. The skills associated with successful mooting, cover the entire range of the domains of human activity: intellectual, physical and emotional. This informative book examines the theories relevant to the development of skills necessary for effective participation in competition moots. By consideration of underlying theories, Mark Thomas and Lucy Cradduck develop unique models of the skills of the cognitive, psychomotor and affective domains and effective team dynamics, emphasising the importance of written submissions. The authors use this analysis to develop a unique integrated model that informs the process of coaching moot teams according to reliable principles. The Art of Mooting distils the theories and principles that support successful moot performances, grounding these in practical examples of how a mooter's skills may be developed and improved. It is an essential guide for moot coaches, law and advocacy students and academics seeking to improve their skills, and new and existing practitioners"--
Foreword 1. Introduction -- 2. The cognitive domain -- 3. The psychomotor domain -- 4. The affective domain -- 5. The moot coach -- 6. Team dynamics -- 7. Written submissions -- 8. International criminal court case study -- 9. Assessing moot performance -- 10. Conclusion and future -- Appendix A -- Appendix B -- Index.
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: moot court; moot courts; e-knihy online; e-books online